Financial relationships and dependencies in Czech secondary school mathematics textbooks - Čechák, Petr (Scientia in educatione, 2023)
This article analyses and compares four sets of Czech secondary school mathematics textbooks from the perspective of financial relationships and dependencies. We claim that understading of financial relationships and dependencies, such as inflation or relationship between potential return of an investment and its riskiness play an important role in financial literacy; this is why they are implicitly present in the Czech Financial Literacy Standard. The importance of the study lies in its focus on the connection between financial education and functional thinking, a link which has been missing in the literature we are familiar with. Functional thinking is an important prerequisite for understanding financial relationships and dependencies. On the other hand, financial topics may also be motivating and suitable contexts for developing functional thinking. Our comparative analyses indicates that Czech secondary mathematics textbooks do not provide teachers and pupils with opportunities to gain insights into the relationships and dependencies in financial education and that potential of the tasks with financial context for developing pupils’ functional thinking is not fully used in the analysed textbooks.